An analysis on the delay of cervical cancer patients in seeking medical check up in Dr. Cipto Mangunkusumo National Central General Hospital Jakarta (Faculty of Medicine Universitas Indonesia, 2003)
In Indonesia, most cervical cancer patients seek medical help after the cancer has reached advanced stage (62 %). This has caused cervical cancer to contribute to 66 % of gynecological deaths. The objective of this study is to find out factors related to the delay of cervical cancer patients in seeking for medical help. This research employs quantitative and qualitative methods. Samples were obtained from all of the new cervical cancer patients who came for the first time between 2000 to 2001 and returned to the Dr. Cipto Mangunkusumo National Central General Hospital Jakarta from August until October 2001. It is concluded that variables significantly correlated with the delay for medical check up are knowledge, attitude, the availability of Pap smear service and husband support. The availability of Pap smear plays as dominant variabel. (Med J Indones 2003; 12: 162-5)